QUESTIONING WOMEN’S FACTUALITY IN TRINITY’S THE NAKED TRAVELER - Riyandari, Angelika (Proceedings of English Linguistics and Literature, 2020)
Women travel writing covers women’s experience of enjoying their independence, learning from the real experience, and exercising the social influence as well as the authority they have. However, women’s travel writings are often not considered worth analyzing as they are styled in a way that tends to be like fiction than a factual report of actual travels. This paper’s objective is to analyze Trinity’s travel writing, The Naked Traveler, in the light of post-truth. It is argued that Trinity’s travel writing is very touristic and is lacked contemplations but her writing is, in a way or another, typical of travel writings. On one hand, Trinity’s travel experiences indeed cannot represent Indonesian women’s experience of traveling since most Indonesian women are not privileged to having access to domestic and overseas travel. In her travel writing, Trinity simplifies the process of planning and executing her travel, thus overlooking the financial limitation and cultural restrictions often faced by Indonesian women to travel. On the other hand, Trinity’s lack of in-depth description and observation in her travel writing should not be regarded as her lack of credibility to present her actual travels. It should be seen as her way of stimulating Indonesian women’s desire to travel, the same aim targeted by many other travel writings.